Wireless Sensor Networks - Chai, Senchun; Wang, Zhaoyang; Zhang, Baihai; Cui, Lingguo; Chai, Runqi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book presents state-of-the-art research advances in the field of wireless sensor networks systems and approaches. It provides in-depth study on a number of major topics such as protocols, localization, coverage control, community detection, small world analysis, etc. Multidisciplinary in nature and closely integrating theory and practice, the book will be of interest to all university researchers, telecommunications engineers and graduate students in wireless sensor networks who wish to learn the core principles, methods, algorithms, and applications. It would help readers rapidly grasp major topics of wireless sensor network and their advances.
Introduction -- Small Worlds and Information Dissemination -- Protocol for Wireless Sensor Networks -- Localization technology for wireless sensor network -- Coverage control in wireless sensor network -- Community Detection Algorithms in Complex Networks.
Keywords: Electrical engineering; Wireless communication systems; Mobile communication systems; Electronic circuits; Communications Engineering, Networks; Wireless and Mobile Communication; Circuits and Systems